Efeito da adição de moléculas anfifílicas na formação de filmes Langmuir e Langmuir-Blodgett de derivados alquilados do politiofeno: aplicação em sensores - Silva, Edilene Assunção da [UNESP] (2014)
In recent decades, concern about the levels of emission of harmful gases has increased considerably, lealding the researchers to develop new materials, devices and technologies for its control. In this vast field, conductive polymer sensors have shown promising results, which can enable the construction of measurement and analysis systems more effective and portable. However, two critical parameters for organic devices are their chemical structure and their solid nanostructure. The electrical properties of these materials have been drastically altered due to electronic coupling between polymer chains which is determined by the type of packing and conformation in the solid state. Moreover, the polythiophenes possess advantageous characteristics compared to other conjugated polymers such as: ease of chemical synthesis and relative ease of functionalization of their size chains. In this context, the aim of this work was to fabricate Langmuir-Blodgett (LB) films of alkylpolythiophene derivates in its regioregular form mixed with stearic acid (SA), in order to obtain good quality films. These films were optical and electrically characterized, and also tested as active layer of volatile organic compounds (VOCs) sensors. LB films of poly(3-butylthiophene), poly(3-hexylthiophene) and poly(3-octylthiophere) containing different percentages of SA in its composition were fabricated, as these pure polymers don't show quality deposition by LB technique. The pressure isotherms of the films were analyzed to assess their molecular characteristics, and to determinate the deposition parameters. These films characterized optically by absorption spectroscopy Ultraviolet-Visible, allowing the evalution of the films growth and organization at the molecular level. Films morphology was analyzed through topographic images obtained in Atomic Force Microscope. LB films deposited onto interdigitated electrodes were used for investigation of electrical...